Kajian Cabaran yang Dihadapi oleh Kontraktor: Pematuhan Peraturan dan Undang-Undang Berkaitan Sisa Pembinaaan - Nadarajan, Kokilavanan; Seow, Ta Wee; Shafii , Haryati (Research in Management of Technology and Business, 2024)
The attitude of non-compliance with regulations and laws regarding construction material waste is increasing in Malaysia, especially in the state of Johor. This phenomenon has caused an increase in negative impacts on the surrounding environment and human welfare. Therefore, the purpose of this study is to investigate factors that can increase the level of contractor compliance with regulations and laws relating to construction residuals. The first objective of this study is to identify the importance of complying with regulations and laws regarding the remainder of coaching. The second objective is to examine the challenges faced by contractors in trying to comply with regulations and laws related to construction waste. Meanwhile, the third objective is to propose methods that can be used to encourage contractors to be more compliant with regulations and laws related to construction waste. This study was carried out using primary and secondary data collection methods. The questionnaire will be distributed to the respondents, which are contractors involved in the construction industry in the state of Johor. The expected result of the study is to be able to solve all three objectives, providing a comprehensive overview of the issues faced by contractors. In conclusion, compliance with regulations related to construction waste is very important for contractors. This study can be used as a reference for future generations and also for contractors in an effort to improve their compliance with regulations and laws related to construction waste.